Richer or more Numerous or both? The Role of Population and Economic Growth for Top Income Shares - Carla Krolage; Andreas Peichl; Daniel Waldenström (Center for Economic Studies and ifo Institute (CESifo), 2018)
When measuring income inequality over long periods of time, accounting for population and productivity growth is important. This paper presents three alternative measures of top income shares that more explicitly account for population and income growth than the standard measure. We apply these measures to long-term income data from the United States and find that the U-shaped inequality trend over the past century holds up, but with important qualifications. Using measures that allow top groups to change not only in relative income but also in group size suggest more accentuated top income share growth since 1980 than when keeping top groups fixed. For earlier historical periods, our analysis shows that choice of income deflator (CPI or GDP) matters greatly. Using distributional national accounts data does not change these results. Altogether, our study's findings suggest that one may want to use several complementary top share measures when assessing long-term income inequality trends.
Keywords: D31; D63; H31; N32; 330; income distribution; inequality; top incomes; growth; measurement